Maternal report of fever from cold or flu during early pregnancy and the risk for noncardiac birth defects, National Birth Defects Prevention Study, 1997–2011. Issue 4 (2nd November 2017) - Waller, Dorothy Kim; Hashmi, Syed Shahrukh; Hoyt, Adrienne T.; Duong, Hao T.; Tinker, Sarah C.; Gallaway, Michael Shayne; Olney, Richard S.; Finnell, Richard H.; Hecht, Jacqueline Tauber; Canfield, Mark A.; ,
Abstract : Background: As maternal fever affects approximately 6–8% of early pregnancies, it is important to expand upon previous observations of an association between maternal fever and birth defects. Methods: We analyzed data from the National Birth Defects Prevention Study, a multistate, case‐control study of major structural birth defects. Telephone interviews were completed by mothers of cases ( n  = 17, 162) and controls ( n  = 10, 127). Using multivariable logistic regression, we assessed the association between maternal self‐report of cold or flu with fever and cold or flu without fever during early pregnancy and 30 categories of non‐cardiac birth defects. Results: Maternal report of cold or flu with fever was significantly associated with 8 birth defects (anencephaly, spina bifida, encephalocele, cleft lip with or without cleft palate, colonic atresia/stenosis, bilateral renal agenesis/hypoplasia, limb reduction defects, and gastroschisis) with elevated adjusted odds ratios ranging from 1.2 to 3.7. Maternal report of cold or flu without fever was not associated with any of the birth defects studied. Conclusions: This study adds to the evidence that maternal fever during early pregnancy is associated with an increased risk for selected birth defects. Elevated associations were limited to mothers who reported a fever, suggesting that it is fever that contributes to the excess risk rather than illnesses associated with it. However, fever may also serve as a marker for more severe infections.